Effect of band alignment and density of states on the collector current in p-Si/n-Si1-yCy - Singh, D.V.
p-Si/n-Si1-yCy/p-Si heterojunction bipolar transistors with varying carbon fractions in the base were grown by rapid thermal chemical vapor deposition (RTCVD), to better understand the potential of Si1-yCy in enhancing the performance of Si-based bipolar technology. The band line-up issues which make Si1-yCy a desirable choice for forming the base region in a p-n-p HBT are discussed. Electrical measurements performed on the p-Si/n-Si1-yCy/p-Si HBTs (y=0.6, 0.8 at.%) are used to extract important information regarding the electronic properties of the Si/Si1-yCy material system, e.g., the bandgap reduction in Si1-yCy compared to Si and minority carrier recombination lifetime in Si1-yCy. Temperature dependent measurements of the collector current were performed to extract the bandgap narrowing at the Si/Si1-yCy heterojunction. This paper includes a detailed analysis of the impact of heavy doping and reduced density of states in Si1-yCy compared to Si on the extraction of the energy bandgap offset, and on the collector current of p-n-p HBTs. The impact of the reduced density of states on the design of p-n-p Si/Si1-yCy HBTs is discussed. The measured value of the energy band offset is (65 meV/at.% C) very close to previously measured values of the conduction band offset at the Si/Si1-yCy heterojunction. The results are thus consistent with a band line-up at the Si/Si1-yCy interface that is dominated by a conduction band offset with little if any valence band offset.
Keywords: RTCVD; Si-SiC-Si.; Si-based bipolar technology; Bandgap narrowing; Bandgap reduction; Chemical vapor deposition; Collector current; Density of states reduction; Electronic properties; Energy bandgap offset; Heavy doping; Minority carrier recombination lifetime; P-n-p HBT; Rapid thermal CVD; Temperature dependent measurements; Si/Si1-yCy material system; p-Si/n-Si1-yCy/p-Si HBTs